2022
DOI: 10.1037/rmh0000148
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the experiences of counselors responding to crisis in rural communities.

Abstract: Responding to clients/students who are threatening harm to self or others is often perceived as a demanding and challenging job for any clinician, especially for those working with limited resources in rural communities. This research explored the experiences of clinical mental health and school counselors who respond to those types of crises within four different states in communities of 9,000 or fewer residents. Using face-to-face and synchronous online interviews, five themes were identified through phenome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 19 publications
1
5
0
Order By: Relevance
“…Despite over two decades' worth of ACEs research, there remains a relative lack of focus on ACEs in rural settings. This dearth is important as rural settings come with unique characteristics and challenges not only to the presentation and intensity of ACEs but also distinct considerations for rural schools and school counselors (Crumb et al, 2021;Frankland, 2021;Fruetel et al, 2022;Keesler et al, 2021;Nichols et al, Theory & Practice in Rural Education, (13)2 | 78 2018; Talbot et al, 2016, Weiss et al, 2023. These considerations will be discussed below.…”
Section: Literature Reviewmentioning
confidence: 99%
See 4 more Smart Citations
“…Despite over two decades' worth of ACEs research, there remains a relative lack of focus on ACEs in rural settings. This dearth is important as rural settings come with unique characteristics and challenges not only to the presentation and intensity of ACEs but also distinct considerations for rural schools and school counselors (Crumb et al, 2021;Frankland, 2021;Fruetel et al, 2022;Keesler et al, 2021;Nichols et al, Theory & Practice in Rural Education, (13)2 | 78 2018; Talbot et al, 2016, Weiss et al, 2023. These considerations will be discussed below.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Additionally, Johnson et al (2022) identified inequitable access to schooling, food, housing, and resources as major ACEs children in rural communities encounter. These factors combined with higher pregnancy-related fatalities, elevated suicidality rates, and the spread of the opioid epidemic, situate children in rural settings in spaces that place them at a higher risk for traumatic experiences (Crumb et al, 2021;Frankland, 2021;Fruetel et al, 2022;NACRHHS, 2018).…”
Section: Trauma In Rural Communitiesmentioning
confidence: 99%
See 3 more Smart Citations